2020
DOI: 10.1891/clinlact-d-19-00017
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding Information and Support Across Multiple Sources: Identifying Opportunities for Coordinated Care

Abstract: To support mothers to breastfeed for recommended durations, information and support are needed from multiple sources. Our previous research indicated not all mothers in our community receive support, with mothers at greater risk of breastfeeding cessation (e.g., lower educational attainment, enrolled in Special Supplemental Nutrition Program for Women, Infants, and Children [WIC]), receiving supports at lower rates. In addition, receiving support was not always linked to breastfeeding outcomes. Building from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…While at first glance it may be surprising that participants who reported their health visitors to be emotionally supportive but informationally unhelpful had longer lactation durations than those who reported both informational and emotional supported positively, this may reflect a lack of need of informational support among these participants [5,50]. Earlier work with this sample has found that support clusters [48], suggesting participants with supportive health visitors were also likely to have ready access to other supporters who may duplicate information, dampening the perceived utility of their advice [51,52]. Affluent mothers, who predominate in our sample, typically have privileged access to support and are likely to breastfeed for longer [53,54].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…While at first glance it may be surprising that participants who reported their health visitors to be emotionally supportive but informationally unhelpful had longer lactation durations than those who reported both informational and emotional supported positively, this may reflect a lack of need of informational support among these participants [5,50]. Earlier work with this sample has found that support clusters [48], suggesting participants with supportive health visitors were also likely to have ready access to other supporters who may duplicate information, dampening the perceived utility of their advice [51,52]. Affluent mothers, who predominate in our sample, typically have privileged access to support and are likely to breastfeed for longer [53,54].…”
Section: Discussionmentioning
confidence: 89%
“…In fact, at times, she made me feel inadequate and gave me incorrect/out-of-date information." Ensuring that health visitors are able to offer effective strategies to navigate challenges and difficulties from the initiation until the cessation of breastfeeding can help facilitate a positive breastfeeding experience [24,52], while those who are formula feeding must also not be forgotten [4]. It is also important for health visitors to quickly and actively refer women to specialist breastfeeding councilors such as lactation consultants -provided they are available-to ensure mothers have access to high quality informational support.…”
Section: Recommendations For Best Practice For Health Visitorsmentioning
confidence: 99%
“…While at first glance it may be surprising that participants who reported their health visitors to be emotionally supportive but informationally unhelpful had longer lactation durations than those who reported both informational and emotional supported positively, this may reflect a lack of need for informational support among these participants [5,50]. Earlier work with this sample has found that support clusters [48], suggesting participants with supportive health visitors were also likely to have ready access to other supporters who may duplicate information, dampening the perceived utility of their advice [51,52]. Affluent mothers, who predominate in our sample, typically have privileged access to support and information, and are likely to breastfeed for longer [53,54].…”
Section: Discussionmentioning
confidence: 89%
“…In fact, at times, made me feel inadequate and gave me incorrect/out-of-date information." Ensuring that health visitors are able to offer effective strategies to navigate challenges and difficulties from the initiation until the cessation of breastfeeding can help facilitate a positive breastfeeding experience [24,52], while those who are formula feeding must also not be forgotten [4]. It is also important for health visitors to quickly and actively refer women to specialist breastfeeding councilors such as lactation consultants -provided they are available-to ensure mothers have access to high quality informational support.…”
Section: Recommendations For Best Practice For Health Visitorsmentioning
confidence: 99%